Efficacy of index of reactivity-liquid sublingual immunotherapy in allergic rhinoconjunctivitis: a systematic review and meta-analysis of randomized studies - Di Bona, Danilo; Di Biase, Andrea; Paoletti, Giovanni; Villani, Rosanna; Serviddio, Gaetano; Cognet-Sicé, Josiane; Scurati, Silvia; Canonica, Giorgio Walter (Frontiers in Allergy, 2025)
IntroductionAllergen immunotherapy (AIT) is a well-established treatment with demonstrated efficacy and safety. However, variability in study outcomes remains a challenge, driven by differences in patient characteristics, study designs, and treatment durations. Moreover, disparities in allergen composition and quality of AIT products across manufacturers contribute to significant heterogeneity, complicating the interpretation of efficacy and safety data. This meta-analysis focuses on assessing the efficacy and safety of a single manufacturer’s liquid sublingual immunotherapy (SLIT) for allergic rhinoconjunctivitis (ARC). By narrowing the scope to one specific product, this study seeks to reduce variability linked to product differences, aligning with recommendations from the World Allergy Organization to improve the reliability of meta-analytic findings.MethodsRandomized controlled trials (RCTs) on index of reactivity (IR) SLIT liquid formulations of various allergens were identified through comprehensive searches in electronic databases (MEDLINE, ISI Web of Science, the Cochrane Library, and ClinicalTrial.gov) up to December 2024, complemented by manual searches. Data on populations, treatments, and outcomes were extracted. Efficacy was evaluated by calculating the standardized mean difference (SMD) for symptoms and medication use. Subgroup analyses were performed by age, allergen type and sensitization status. Asthma comorbidity, dose and duration of SLIT were evaluated using meta-regression.ResultsA total of 25 RCTs (1,830 patients) provided data on symptom scores (SS), and 19 RCTs (1,555 patients) reported on medication scores (MS). Analysis revealed that IR-SLIT-liquid was significantly more effective than placebo in reducing both SS (SMD: −0.30; 95% CI: −0.41 to −0.18; P < 0.0001) and MS (SMD: −0.51; 95% CI: −0.72 to −0.29; P < 0.0001). Efficacy outcomes were consistent regardless of factors such as age, allergen type (grass, house dust mites, trees, weeds), sensitization status, asthma presence, or cumulative dose, while longer treatment durations were associated with improved efficacy. No significant adverse events were reported.DiscussionThis meta-analysis underscores the clinical effectiveness and safety of IR-SLIT-liquid, confirming its role as a reliable etiologic treatment for patients with ARC, for all allergens and age groups. The effect size is comparable to other immunotherapy options. The low rates of adverse events and treatment withdrawals highlight favorable tolerability and high level of patient adherence.Systematic Review Registrationhttps://inplasy.com/wp-content/uploads/2025/01/INPLASY-Protocol-7305.pdf, INPLASY 202510049